Free radical scavenging activity, total phenolic and flavonoid content studies of Phaleria macrocarpa (Sheff).Boeri. fruits. - Muhammad Anwar Ahmad (2016)
The fruit of God's crown is traditionally used to treat flu, rheumatism and can be used for heart disease. It also contains antioxidants that can treat with cancer diseases. Each of the part from the plant is used by the local people to treat diseases. The leaves traditionally used to treat dysentery and allergy. The traditionally preparation uses water extraction. Antioxidant, anti-inflammatory and antimicrobial properties have been indicated by screened in vitro and can be used to developed drugs or dietary supplements. Soxhlet was used to extract the compound using ethanol and then undergoes liquid-liquid partition using hexane, chloroform, ethyl acetate and butanol. DPPH assay and total phenolic and flavonoid content assay were used to determine the antioxidant activities, phenolic and flavonoid content. The data were then analyzed by using one-way analysis of variance (ANOVA) using SPSS, to see the relationship between each samples and correlation of antioxidant activities between phenolic and flavonoid content. ANOVA test of DPPH, total phenolic and flavonoid content assay shown they were significant results. Correlation of antioxidant activities between phenolic and flavonoid content showed there was other compound contributed to the antioxidant activities. The finding suggested studies should be further analysed to find haxane and chloroform can extract non-polar phenolic content and detect if there is other compound contributed to antioxidant to antioxidant activities. Phytochemical studies should be studied in Mahkota Dewa fruits to determine the compound in the fruits.